Assessment of treatment outcomes of visceral leishmaniasis (VL) treated cases and impact of COVID-19 on VL management and control services in Bangladesh - Shomik Maruf; Soumik Kha Sagar; Md Utba Rashid; Md Rasel Uddin; Debashis Ghosh; Prakash Ghosh; Rupen Nath; Abu Nayeem Mohammad Sohel; M.M. Aktaruzzaman; Md. Nazmul Islam; Megha Raj Banjara; Axel Kroeger; et al. (Elsevier, 2023)
Background: COVID-19 has largely impacted the management of Visceral leishmaniasis (VL), like several other Neglected Tropical Diseases. The impact was particularly evident in Lower and Middle-Income countries where the already inadequate healthcare resources were diverted to managing the COVID-19 pandemic. Bangladesh achieved the elimination target for VL in 2016. To sustain this success, early diagnosis and treatment, effective vector control, and periodic surveillance are paramount. However, the specific control measures for VL in Bangladesh that were hampered during COVID-19 and their extent are unknown. Methods: This study aimed at identifying the gaps and challenges in the follow-up of treated VL patients by interviewing both the treated VL cases and their health service providers. We followed VL cases treated between 2019 and 2020 in five VL endemic subdistricts (upazilas) both retrospectively and prospectively to monitor clinical improvement, relapse, or other consequences. Moreover, interviews were conducted with the health service providers to assess the impact of COVID-19 on VL case detection, treatment, reporting, vector control operations, and logistic supply chain management. Results: There was no added delay for VL diagnosis; however, VL treatment initiation and reporting time increased almost two-fold due to COVID-19. Indoor Residual Spraying activity was significantly hampered due to a shortage of insecticides. Out of 44 enrolled and treated VL patients, two relapsed (4.5 %), two developed Para Kala-Azar Dermal Leishmaniasis (4.5 %), and three (6.8 %) Post Kala-Azar Dermal Leishmaniasis (PKDL). The health service providers highlighted patients` unwillingness to visit the hospital, financial constraints, and distance from the hospitals as the main reasons for missed follow-up visits (20.5 %). Building good communication in the community, awareness schemes, and incentive-based approaches were suggested as possible solutions to mitigate these problems. Conclusion: Long-term follow-up is required for the early detection and management of VL relapse and PKDL cases. Effective vector control measures, capacity development, and identification of new VL hotspots are pivotal in the VL endemic regions to sustain the elimination goal.